Evaluation of some key features of Islamic finance in non-Islamic economies: Bulgarian perspective - Kamdzhalov, Miroslav (European Journal of Islamic Finance, 2022)
In recent years Islamic finance has steadily increased in popularity. In this respect, the research sets itself a task to evaluate some key features of Islamic finance in the Bulgarian financial market. To achieve this Fuzzy AHP method and deductive, inductive reasoning are used. The results show that the understanding of Islamic banking principles in Bulgaria has social banking characteristics. These characteristics are related to consumer expectations that can be defined as fundamental or basic such as the provision of a financial product or service, interest-free loans and securities with a social function for stakeholders. The results are unique and representative of the Bulgarian experts’ opinions, processed scientifically to showcase the potential of Islamic finance in the local financial market. Hitherto, presumably, no other research concerning Bulgaria has done such an evaluation. The main limitation of this research is the lack of Islamic financial institutions operating in the Bulgarian market. The research relies on the knowledge of local banking experts on Islamic finance principles. The findings can be applied in the decision-making process in the Islamic finance context.